Proceeding of the 4th International Seminar on Linguistics (ISOL-4) 2019
DOI: 10.2478/9783110680027-038
|View full text |Cite
|
Sign up to set email alerts
|

Topics and Reasons for Violating the Maxim of Quantity when Implicature is Generated

Abstract: Testing a theory is required to give room for the theory to improve and develop. This research is conducted for this reason. Specifically, this research is designed to identify the topics and reason of the violation of the maxim of quantity when the implicature is generated to complement the writer's earlier research. The data were collected by taking notes of the implicature produced by the participants during lunchtime at Universitas Katolik De La Salle Manado. The result shows that in the violation of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, the researcher also found several other researcher who had studied about quantity maxim violation. Khosravizadeh & Sadehvandi (2011), Ngenget (2019) found that the reasons of violating the maxim was mostly in order to share information. In movie, Khosravizadeh & Sadehvandi (2011).…”
mentioning
confidence: 99%
“…Moreover, the researcher also found several other researcher who had studied about quantity maxim violation. Khosravizadeh & Sadehvandi (2011), Ngenget (2019) found that the reasons of violating the maxim was mostly in order to share information. In movie, Khosravizadeh & Sadehvandi (2011).…”
mentioning
confidence: 99%